2019
DOI: 10.29103/jak.v6i1.1820
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengukuran Kinerja Dengan Menggunakan Konsep Value for Money Pada Pemerintah Kota Lhokseumawe: (Studi Kasus Pada Dpkad Kota Lhokseumawe Periode 2014-2016)

Abstract: This study aimed to determine the performance  of the Office of Revenue Finance and Regional Assets (DPKAD) Lhokseumawe City by using the concept of Value For Money. This research was conducted by taking data for 3 years, from 2014 to 2016. This research used secondary data. The method of data analysis used is descriptive qualitative analysis method. Based on the research  result by using Value For Money concept based on 3 main elements such as economic, efficiency and effectiveness show that: Economic ratio, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…According to (Ocean and Sugeng, 2020); (Hairiyah et al, 2018) DAK has an impact on capital expenditure, unlike (Syukri and Hinaya, 2019); (Eksandy et al, 2015) who say otherwise. According to (Perdana et al, 2020); (Indrayani & Khairunnisa, 2018) economic impact on capital expenditure, in contrast to (Enre, 2020); (Indriaswari, 2017) which states otherwise. According to (Ardhini and Handayani, 2011) efficiency has an impact on capital expenditure, in contrast to (Tamawiwy et al, 2016); (Indiyanti and Rahyuda, 2018) who found the opposite.…”
Section: Preliminarymentioning
confidence: 99%
“…According to (Ocean and Sugeng, 2020); (Hairiyah et al, 2018) DAK has an impact on capital expenditure, unlike (Syukri and Hinaya, 2019); (Eksandy et al, 2015) who say otherwise. According to (Perdana et al, 2020); (Indrayani & Khairunnisa, 2018) economic impact on capital expenditure, in contrast to (Enre, 2020); (Indriaswari, 2017) which states otherwise. According to (Ardhini and Handayani, 2011) efficiency has an impact on capital expenditure, in contrast to (Tamawiwy et al, 2016); (Indiyanti and Rahyuda, 2018) who found the opposite.…”
Section: Preliminarymentioning
confidence: 99%
“…Value for money pengukuran kinerja untuk mengukur ekonomi, efisiensi dan efektivitas suatu kegiatan, program dan organisasi. Manfaat yang dikehendaki dalam pelaksanaan value for money pada organisasi sektor publik yaitu : ekonomis (hemat cermat), efisiensi (berdaya guna) dan efektif (berhasil guna) (Indrayani, 2018).…”
Section: Value For Moneyunclassified
“…One of the previous studies from Septariani (2018) found that based on the calculation of the concept of Value for Money, financial management was economical, efficient, and effective so that good governance was realized. Another study from Indrayani & Khairunnisa(2018) found that the government of Lhokseumawe (Study Case at DPKAD Lhokseumawe in 2014-2016) has manage their budget economically, efficient, but still ineffective. The difference with other research is the focus of this research on the realization of budget accountability at the BPKAD of Banjar Regency with the calculation of the fiscal year 2016 -2019.…”
Section: Introductionmentioning
confidence: 99%